First record of the chytrid fungus in Lithobates catesbeianus from Argentina: exotic species and conservation - Ghirardi, Romina (2011)
Chytridiomycosis, a disease caused by the chytrid fungus Batrachochytrium dendrobatidis (B.d.), is recognized as one of the major factors of amphibian decline. Global trade of amphibians has been identified as one of the causes of B.d. spread, involving hundreds of species world wide. In this work we detected the presence of B.d. through histological examination on 5 out of 9 analyzed specimens of bullfrogs (Lithobates catesbeianus) from a farm in Santa Fe City (Argentina), deposited since 1993 in the herpetological collection of the Provincial Museum of Natural Sciences “Florentino Ameghino”. Our finding represents the oldest record of B.d. for Argentina and the first case of the chytrid fungus infecting the exotic bullfrog in this country. We emphasize the importance of determining and monitoring the distribution and spread of B.d in Argentina, particularly in areas where feral bullfrog populations have already been identified.